Making Latin American forest work for people and nature: Essential forest policies for Latin America - Mery, Gerardo (2009)
Making Latin American Forests Work for People and Nature: Essential Forest Policies for Latin America was prepared jointly by the World Forests, Society and Environment (WFSE) Project — a Special Project of the International Union of Forest Research Organizations (IUFRO) — and the Tropical Agricultural Research and Higher Education Center (CATIE). It also received support from the Finnish Forestry Research Institute (METLA) and the generous financial support of the Ministry of Foreign Relations of Finland. The purpose of this document is to offer a shared vision of recommendations for essential policies required to ensure that Latin America’s forest resources are sustainably used and conserved, both for the benefit of people and for the protection of nature.The brief policy recommendations outlined in this publication are based on extensive scientific evidence compiled by the authors and were selected as a result of a long and creative discussion involving 18 researchers from this region at the end of March 2007 in Turrialba, Costa Rica. A synopsis was subsequently prepared by seven authors who took part in that meeting and was reviewed by numerous specialists in forest issues, to whom the authors express their sincere thanks. In addition to the seven authors, the coauthors also made valuable contributions to this work, participating actively in the 2007 discussion and serving as reviewers of the final document.